Hearing others’ pain: neural activity related to empathy - Lang, Simone; Yu, Tao; Markl, Alexandra; Müller, Friedemann; Kotchoubey, Boris (Cognitive, affective, & behavioral neuroscience, 2011)
The human voice is one of the principal conveyers of social and affective communication. Recent neuroimaging studies have suggested that observing pain in others activates neural representations similar to those from the first-hand experience of pain; however, studies on pain expressions in the auditory channel are lacking. We conducted a functional magnetic resonance imaging study to examine brain responses to emotional exclamations of others’ pain. The control condition comprised positive (e.g., laughing) or negative (e.g., snoring) stimuli of the human voice that were not associated with pain and suffering. Compared to these control stimuli, pain-related exclamations elicited increased activation in the superior and middle temporal gyri, left insula, secondary somatosensory cortices, thalamus, and right cerebellum, as well as deactivation in the anterior cingulate cortex. The left anterior insular and thalamic activations correlated significantly with the Empathic Concern subscale of the Interpersonal Reactivity Index. Thus, the brain regions involved in hearing others’ pain are similar to those activated in the empathic processing of visual stimuli. Additionally, the findings emphasise the modulating role of interindividual differences in affective empathy.